Inovasi Diversifikasi Produk Pangan Fungsional Berbasis EmponEmpon Lokal sebagai Strategi Ketahanan Pangan di Kelurahan Kedungkeris Kecamatan Nglipar, Gunung Kidul - Masrukan; Elisa Tri Nursari; Eman Darmawan; Bahri (Universitas Widya Mataram, 2025)
The development of product diversification based on empon-empon by the Seger Waras Agricultural Industry Group (KITSW) in Kedungkeris Village, Nglipar District, Gunungkidul Regency, faces several challenges, particularly in post-harvest handling, standardized herbal product processing, and conventional marketing strategies. Through the Community Partnership Program (PKM), the implementing team provided solutions via several forms of assistance: 1) training and mentoring in optimal post-harvest handling of empon-empon 2) training and mentoring in the production of simplisia and functional beverages based on empon-empon, and 3) training and mentoring in business management and digital marketing strategies. As a result of the program, proper post-harvest handling and processing practices were successfully implemented, leading to the production of simplisia and functional beverages under the brand “Saras Kasuri Toga”. Marketing efforts were also improved, not only through conventional methods but also via technology-based platforms such as the website https://kedungkeris-mart.com). This program has contributed to enhancing the competitiveness and welfare of the farmer group in managing their business, strengthening local food security, and creating new employment opportunities for the surrounding community. Keywords: diversification, local empon-empon, functional food, food sovereignty